Impagidinium detroitense and I.? diaphanum: Two new dinoflagellate cyst species from the Pliocene of the North Pacific Ocean, and their biostratigraphic significance - Zorzi, Coralie; Head, Martin J.; Matthiessen, Jens; De Vernal, Anne (Review of Palaeobotany and Palynology, 2019)

Millennial‐Scale Climate Variability and Dinoflagellate‐Cyst‐Based Seasonality Changes Over the Last ~150 kyrs at “Shackleton Site” U1385 - Datema, Mariska; Sangiorgi, Francesca; De Vernal, Anne; Reichart, Gert‐Jan; Lourens, Lucas J.; Sluijs, Appy (Paleoceanography and Paleoclimatology, 2019)
Abstract During the last glacial period, climate conditions in the North Atlantic region were determined by the alternation of relatively warm interstadials and relatively cool stadials, with superimposed rapid warming (Dansgaard‐Oeschger) and cooling (Heinrich) events. So far little is known about the impact of these rapid climate shifts on the seasonal variations in sea surface temperature (SST) within the North Atlantic region. Here, we present a high‐resolution seasonal SST record for the past 152 kyrs derived from Integrated Ocean Drilling Program “Shackleton” Site U1385, offshore Portugal. Assemblage counts of dinoflagellates cysts (dinocysts) in combination with a modern analog technique (MAT), and regression analyses were used for the reconstructions. We compare our records with previously published SST records from the same location obtained from the application of MAT on planktonic foraminifera. Our dinocyst‐based reconstructions confirm the impression of the Greenland stadials and interstadials offshore the Portuguese margin and indicate increased seasonal contrast of temperature during the cold periods of the glacial cycle (average 9.0 °C, maximum 12.2 °C) with respect to present day (5.1 °C), due to strong winter cooling by up to 8.3 °C. Our seasonal temperature reconstructions are in line with previously published data, which showed increased seasonality due to strong winter cooling during the Younger Dryas and the Last Glacial Maximum over the European continent and North Atlantic region. In addition, we show that over longer time scales, increased seasonal contrasts of temperature remained characteristic of the colder phases of the glacial cycle. , Key Points New high‐resolution dinocyst‐based summer and winter SST record from IODP “Shackleton” Site U1385 for the last 150 kyrs is presented Dinocyst‐based SST confirms the D‐O cycles and HEs at Site U1385 Increased seasonal contrast of SST (up to 12 degree C) during cold periods of the glacial cycle related to strong winter cooling is shown

Postglacial paleoceanography and paleoenvironments in the northwestern Barents Sea - Ivanova, Elena; Murdmaa, Ivar; De Vernal, Anne; Risebrobakken, Bjørg; Peyve, Alexander; Brice, Camille; Seitkalieva, Elvira; Pisarev, Sergey (Quaternary Research, 2019)
Abstract The Barents Sea offers a suitable location for documenting advection of warm and saline Atlantic Water (AW) into the Arctic and its impact on deglaciation and postglacial conditions. We investigate the timing, succession, and mechanisms of the transition from proximal glaciomarine to marine environment in the northwestern Barents Sea. Two studied sediment cores demonstrate diachronous retreat of the grounded ice sheet from the Kvitøya Trough (core S2528) to Erik Eriksen Trough (core S2519). Oxygen isotope records from core S2528 depict a two-step pattern, with lower δ 18 O values prior to the Younger Dryas (YD), and higher values afterward because of advection of the more saline, 18 O-enriched AW. At this location, subsurface AW penetration increased during the Allerød and YD/Preboreal transition. In the study area, foraminiferal and dinocyst data from the YD interval suggest cold conditions, extensive sea-ice cover, and brine formation, along with the flow of chilled AW at subsurface and the development of a high-productivity polynya in the Erik Eriksen Trough. Dense winter sea-ice cover with seasonal productivity persisted in the Kvitøya Trough area during the early Holocene, whereas surface warming seems to have occurred during the middle Holocene interval.

Challenges and research priorities to understand interactions between climate, ice sheets and global mean sea level during past interglacials - Capron, Emilie; Rovere, Alessio; Austermann, Jacqueline; Axford, Yarrow; Barlow, Natasha L.M.; Carlson, Anders E.; De Vernal, Anne; Dutton, Andrea; Kopp, Robert E.; McManus, Jerry F.; Menviel, Laurie; Otto-Bliesner, Bette L.; et al. (Quaternary Science Reviews, 2019)